2021
DOI: 10.1038/s41419-020-03310-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal extracellular vesicle derived miR-98 prevents salvageable neurons from microglial phagocytosis in acute ischemic stroke

Abstract: Extracellular vesicles (EVs), as a novel intercellular communication carrier transferring cargo microRNAs (miRNAs), could play important roles in the brain remodeling process after ischemic stroke. However, the detailed mechanisms involved in EVs derived miRNAs-mediated cellular interactions in the brain remain unclear. Several studies indicated that microRNA-98 (miR-98) might participate in the pathogenesis of ischemic stroke. Here, we showed that expression of miR-98 in penumbra field kept up on the first da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 60 publications
0
43
0
Order By: Relevance
“…Four-week minocycline treatment at 4 days after tMCAO decreased the number of activated microglia and increased the number of BrdU + /NeuN + cells ( Liu et al, 2007 ). Overexpressing miR-98 inhibited microglial phagocytosis to attenuate neuronal death in the penumbra area at 3 days after tMCAO ( Yang et al, 2021 ). However, microglial phagocytotic receptor TREM2 knockout mice showed less tissue resorption and a larger lesion area, along with severe limb bias, which suggested that microglial phagocytosis improved synapse and axon regeneration after injury ( Werneburg et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Four-week minocycline treatment at 4 days after tMCAO decreased the number of activated microglia and increased the number of BrdU + /NeuN + cells ( Liu et al, 2007 ). Overexpressing miR-98 inhibited microglial phagocytosis to attenuate neuronal death in the penumbra area at 3 days after tMCAO ( Yang et al, 2021 ). However, microglial phagocytotic receptor TREM2 knockout mice showed less tissue resorption and a larger lesion area, along with severe limb bias, which suggested that microglial phagocytosis improved synapse and axon regeneration after injury ( Werneburg et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was attributed to chemokine CXC motif ligand 1 (CXCL1), a target gene of miR-181-3p, which was downregulated by this miR in astrocytes [ 40 ]. Furthermore, miR-98 derived from Ne-Exos acts as a post-ischemic endogenous protective factor by inhibiting microglial phagocytosis via the targeting of platelet-activating factor receptor (PAFR), thereby attenuating ischemia-induced neuronal death [ 41 ]. In addition, Xu et al revealed that neurons transfer miR-132 to endothelial cells via secreting exosomes.…”
Section: Preclinical Studies Of Exosomes Derived From Nvu Componentsmentioning
confidence: 99%
“…The undesired effects of excessive efferocytosis of distressed yet viable neurons can be prevented by therapies focused on administration of extracellular vesicles containing molecules such as miR-98. In a model of ischemic stroke, miR-98-loaded extracellular vesicles prevented the stressed but viable neurons from microglial phagocytosis [ 143 ]. The miR-98 acts via the platelet activating factor receptor (PAFR) that mediates efferocytosis as observed during engulfment of excitatory synapses of hippocampus in a model of experimental auto-immune encephalomyelitis [ 144 ] or apoptotic thymocytes in cell culture [ 145 ].…”
Section: Efferocytosis As a Therapeutic Modality In Strokementioning
confidence: 99%